Morphological and histological characteristics of ovaries from two genetic groups of guinea pigs (Cavia porcellus) from South America - Fernández, Estefanía A. (2022)
This study aimed to describe morphological and histological characteristics of ovaries of two genetic groups of guinea pigs from Latin America. Ovaries from 20 improved and 20 native guinea pigs were collected after slaughtering. One ovary from each animal was weighed, measured, counted for visible follicles on the ovarian surface, and used for subsequent oocyte collection by the slicing method. Contralateral ovaries were used to prepare histological sections and quantify follicles. Body and ovary weight and ovary length were significantly greater in improved than in native guinea pigs (p<0.01). Ovarian weight was greater in diestrus than in proestrus (p=0.0632) only in improved animals. The number of primordial, primary, secondary, and total follicles did not differ between genetic groups. The number of antral follicles was significantly greater in improved than in native guinea pigs. The thickness of zona pellucida and oocyte diameter did not differ between groups. The thickness of the zona pellucida was significantly greater in oocytes of category A than B and C in both groups of guinea pigs. In conclusion, ovaries from improved guinea pigs were heavier and longer than those from native animals. The number of antral follicles was greater in improved than native guinea pigs. Zona pellucida thickness and oocyte diameter were similar in both groups of guinea pigs.